Long-term Result of Surgical Correction of Ischemic Mitral Insufficiency in a Patient With Posterior Basal Post-Infarction Left Ventricular Aneurysm - V. A. Sapunov; S. Y. Boldyrev; I. P. Pavlenko (Неотложная медицинская помощь, 2021)
The article presents a long-term result of surgical correction of ischemic mitral valve insufficiency, left ventricle inferior wall reconstruction.